(untitled) (Comillas Journal of International Relations, 2019)
This article seeks to analyse the intervention of the most influential business organization of France, the Conseil national du patronat français (CNPF), current MEDEF, during the negotiations for the accession of Spain into the EEC (1977-1986). The following pages are an approximation from the historiographic perspective to the participation and influence of non-governmental actors –employers organizations– in the field of International Relations. The favourable opinion of the CNPF on Spain’s application for accession offers an alternative perspective of France’s policy toward Spain in the context of the second Community enlargement.